PERAN PENDIDIKAN AGAMA KRISTEN DALAM KELUARGA TERHADAP PERILAKU GENERASI MUDA - IRING LALO; NORYATI NORYATI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2021)
Education in the family in the family is our worship without limits to God who is worshiped, there is no limit to both the place and time we want to use, because education in schools and churches can be said to be limited, Christian religious education in this family is real education given to children, The purpose of education in the family is to lead the child's relationship to God, one of the main goals of Christian Religious Education in the family in order to train the cohesiveness of parents, both father and mother in educating their children, to make it visible The harmony and warmth of the family in educating their children with love, so that the children also feel the harmony of their families in seeking God in the family, besides that parents can see the development of their children, as well as provide good examples for their children.